Mitigating Screen Addiction in Early Childhood Using Value-Based Family Counseling in Ancient Javanese Texts - Fitriyah, Fifi Khoirul; Ramli, M.; Kurniawan, Nanda Alfan; Ngussa, Baraka Manjale; Mamat, Nordin Bin (Jurnal Kajian Bimbingan dan Konseling, 2025)
Gadget addiction is often associated with poor social interaction skills, anxiety, and physical health. However, few studies have addressed the issue of gadget addiction in early childhood. The purpose of this study was to evaluate a family counseling model that internalizes values from ancient Javanese texts to reduce gadget addiction in early childhood. The ancient Javanese text used was Kakawin Sutasoma, which describes the meaningful journey of Prince Sutasoma. This study was an experiment with a single-subject ABA design. The results showed positive developments in all three cases. In Case 1, reducing gadget time resulted in improved social skills in the subjects. In Case 2, limiting gadget time resulted in improved sleep quality in the subjects. In Case 3, reducing gadget use combined with prosocial skills training reduced aggressive behavior and improved emotional regulation skills. Thus, it can be concluded that internalizing the values of Kakawin Sutasoma in family counseling is effective in reducing gadget use, thus impacting social skills in early childhood. Recommendations for future researchers include involving adequate samples and using experimental designs to increase the generalizability of the research results.